The relationship between household activities and the exclusive breastfeeding period in mothers breastfeeding babies aged 6-12 months in Sumberpucung Village, Malang regency - Rizkiyah, Nur Kholifatur (Edelweiss Applied Science and Technology, 2025)
Household activities are a number of activities that must be completed by someone who is a housewife. The impact is a lack of time to rest, if experienced by mothers who are breastfeeding, this will cause milk production to decrease due to work fatigue. If a breastfeeding mother experiences work fatigue, there will be a blockade of the letdown reflex. An imperfect letdown reflex will cause a buildup of milk in the alveoli, this is due to the release of adrenaline (epinephrine) which causes vasoconstriction of the alveolar blood vessels so that it will inhibit oxytocin from reaching the target organs of the myoepithelium. So breastfeeding mothers need to have time to rest. This study aims to determine the relationship between household activities and the breastfeeding period in mothers breastfeeding babies aged 6-12 months. The method used is correlation analysis with cross sectional ratio. The research sample was 45 mothers breastfeeding babies aged 6-12 months in Sumberpucung Village, Malang Regency in May 2018. The instruments used were the Harvard Scale family activity profile sheet and interview guide. The research results showed that the majority of respondents, 75.5%, were in the heavy work category (>10 hours/day) and 80% were not exclusively breastfed. The data was analyzed using Spearman Rank correlation, the results obtained were an rho value of -0.387, meaning there was a significant relationship between household activities and the period of exclusive breastfeeding. To overcome the impact of household activities on the exclusive breastfeeding period, it is hoped that you can manage your time between doing household chores, especially during the exclusive breastfeeding period.